New questions arise: are bibliometric indicators adequate for evaluating the scientific production of the Social Sciences and Humanities? - Pinto, Maria João; Fernandes, Sofia (Qualitative and Quantitative Methods in Libraries, 2017)
This study aims to examine the criteria and bibliometric indicators in the evaluation of scientific production and determine the appropriateness of these within the Social Sciences and Humanities. In an international context, higher education institutions, research centers and groups and funding agencies plan to evaluate qualitatively and quantitatively the scientific production from all areas based on the same indicators. In fact, scientific areas differ from their nature, publication types to the geographical area in publishing, among other factors. Furthermore, standardization of criteria and indicators for general unique and all scientific truth may not reflect the results of research and publication of each area. This article collects and analyzes the criteria and indicators for evaluating qualitative and quantitative effects. On the other hand, it makes a collection of information published on the application of this model to evaluate the areas of Social Sciences and Humanities. We sought to information published by information professionals dedicated to the evaluation of scientific literature and also reports and pronouncements of research centers and higher education institutions. Based on a survey of published information in this area, we tried to identify possible shortcomings of this evaluation model, these areas specifically. Only with an understanding of research and publication in its field, it may be possible to refute the assessment model in place and also consider the possibility and feasibility of presenting a proper assessment model. This is a necessity in the Humanities and Social Sciences that is demonstrated in the literature.